2020
DOI: 10.1002/ccd.29381
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and outcomes of transcatheter coil embolization for various coronary artery lesions: Single‐center 12‐year experience

Abstract: Objective Determining the outcomes of transcatheter coil embolization (TCE) for several coronary artery lesions. Background TCE has been used as a treatment modality for various lesions in the coronary circulation. However, data on the efficacy and safety of TCE to treat coronary artery fistula (CAF), left internal mammary artery (LIMA) side‐branch, coronary artery perforation (CAP), coronary artery aneurysm (CAA), and coronary artery pseudoaneurysm (CAPA) are limited. Methods We conducted a retrospective, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…3,15, 16 Recently, Abdelfattah et al reported successful angiographic transcatheter coil embolization in 88% of CAF cases. 17 In the present study, tortuous fistulas were observed in 91% (20/22) of LCX-CAF patients. However, coils were used for TCC in only 18.2% (4/22) of cases.…”
Section: Limited Data For Tcc Of Lcx-cafsupporting
confidence: 54%
“…3,15, 16 Recently, Abdelfattah et al reported successful angiographic transcatheter coil embolization in 88% of CAF cases. 17 In the present study, tortuous fistulas were observed in 91% (20/22) of LCX-CAF patients. However, coils were used for TCC in only 18.2% (4/22) of cases.…”
Section: Limited Data For Tcc Of Lcx-cafsupporting
confidence: 54%
“…5,[27][28][29] Unlike main vessel CAP which can be treated with covered stents, distal perforations are often too small to utilize covered stent and are usually treated by embolization using coils or other methods such as fat embolization. 2,5,27,30 There has been a significant increase in CTO PCI and complex procedures that led to an increase in the risk of complications, particularly perforations, and in turn to an increase in the need for coronary coils. The risk of perforation increases further in retrograde CTO PCI as compared to antegrade approach, making it an independent predictor of risk for perforation in CTO procedures.…”
Section: Acute Indications For Coil Embolizationmentioning
confidence: 99%
“…Distal perforations typically occur due to wire migration and is commonly associated with the use of hydrophilic, polymer‐jacketed wires, (88.9% of CAP reported as due to hydrophilic wires) 5,27–29 . Unlike main vessel CAP which can be treated with covered stents, distal perforations are often too small to utilize covered stent and are usually treated by embolization using coils or other methods such as fat embolization 2,5,27,30 …”
Section: Acute Indications For Coil Embolizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the journal, Abdelfattah et al describe the outcomes of 41 coil embolizations performed over a 12-year period at a tertiary cardiac catheterization laboratory. 1 Coil embolization represented 0.034% of PCIs and was performed for various indications: 25 coronary artery fistulas, 7 left internal mammary artery side branches, 5 coronary artery perforations, 2 coronary artery aneurysms and 2 coronary artery pseudoaneurysms. Successful closure was achieved in 87.8% of cases with only one adverse event directly related to coil embolization due to coil migration requiring re-intervention at 3 months.…”
mentioning
confidence: 99%